Magma chamber growth models in the upper crust: A review of the hydraulic and inertial constraints - Aragon, Eugenio (2019)
Finite volumes of magma moving in confinement, store hydraulic potential energy for the generation, control and transmission of power. The Pascal´s principle in a hydraulic jack arrangement is used to model the vertical and lateral growth of sills. The small input piston of the hydraulic jack is equivalent to the feeder dike, the upper large expansible piston equivalent to the magmatic chamber and the inertial force of the magma in the dike is the input force. This arrangement is particularly relevant to the case of sills expanding with blunt tips, for which rapid fracture propagation is inhibited. Hydraulic models concur with experimental data that show that lateral expansion of magma into a sill is promoted when the vertical ascent of magma through a feeder dike reaches the bottom contact with an overlying, flat rigid-layer. At this point, the magma is forced to decelerate, triggering a pressure wave through the conduit caused by the continued ascent of magma further down (fluid-hammer effect). This pressure wave can provide overpressure enough to trigger the initial hydraulic lateral expansion of magma into an incipient sill, and still have enough input inertial force left to continue feeding the hydraulic system. The lateral expansion underneath the strong impeding layer, causes an area increase and thus, further hydraulic amplification of the input inertial force on the sides and roof of the incipient sill, triggering further expansion in a self-reinforcing process. Initially, the lateral pressure increase is larger than that in the roof allowing the sill to expand. However, expansion eventually increases the total integrated force on the roof allowing its uplift into either a laccolith, if the roof preserves continuity, or into a piston bounded by a circular set of fractures. Hydraulic models for shallow magmatic chambers, also suggest that laccolith-like intrusions require the existence of a self-supported chamber roof. In contrast, if the roof of magmatic chambers loses the self-supporting capacity, lopoliths and calderas should be expected for more or less dense magmas, respectively, owing to the growing influence of the density contrast between the host rock and the magma.